Efektivitas Whatsapp sebagai Media Komunikasi Interpersonal kepada Pasangan - Khiyaroh, Intihaul; Eko Nurul Mufid; Putra Andika Yoga Pratama (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2024)
In this digital era, WhatsApp has become a popular interpersonal communication platform, including for couples. WhatsApp, as one of the most popular instant messaging applications in the world, including Indonesia, has brought about significant changes in the dynamics of communication science. WhatsApp provides various features such as text messages, voice calls, and video calls, which allow couples to stay connected in real-time even if they are far apart. Interpersonal communication via WhatsApp makes it easy to interact, which was initially done face to face, can now be done virtually with communication technology that continues to develop. This research aims to analyze the effectiveness of WhatsApp as a medium for interpersonal communication for couples. The method used is descriptive qualitative with a literature review approach. Data was taken from journal articles, books, research reports, and other academic sources that discuss the use of WhatsApp in couples' interpersonal communication. The research results show that WhatsApp is an application that is often used in interpersonal communication between couples because of its features that allow sending text messages, voice and video calls, as well as voice and video messages. WhatsApp provides convenience in high frequency and intensity of use, which can strengthen emotional ties and provide a sense of presence even when physically apart. The benefits of using WhatsApp include convenience, accessibility, creative emotional expression, and improved relationship quality. However, there are challenges such as misunderstandings due to a lack of nonverbal cues, over-reliance on WhatsApp, and privacy and security issues. Factors that influence the effectiveness of communication via WhatsApp include the level of trust between partners and digital competence in using this application. In conclusion, WhatsApp is an effective communication tool for couples noting that challenges such as misunderstanding and dependency need to be overcome. The level of trust and digital competence are important factors that influence the effectiveness of communication via WhatsApp. This research provides insight for couples on how to use WhatsApp effectively in their interpersonal communication as well as providing a basis for further research.